Eksistensi dan Posisi Perempuan Dalam Politik Kekuasaan: Perspektif Tafsir Qs. An-Nahl Ayat 97 - Miranda, Fazira (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2025)
This article examines the relationship between gender existence and women's roles in power politics through Surah An-Nahl verse 97. The verse affirms equal reward for righteous deeds regardless of gender, offering a theological basis for gender equality. Traditional interpretations often emphasize complementary roles between men and women, which sometimes restrict women's participation in politics. In contrast, contemporary scholars argue for an egalitarian reading, supporting women's active involvement in leadership and decision-making. The study reviews historical examples of women's participation in early Islamic societies and compares them to contemporary developments, particularly highlighting progress in the MENA region and South Asia. Case studies from Pakistan, Indonesia, Bangladesh, and Kyrgyzstan show how Muslim women leaders navigate religious, cultural, and political challenges. The article also discusses the role of Islamic feminism in reinterpreting religious texts to advocate for women's political rights and leadership. Islamic feminist scholarship challenges patriarchal readings and promotes a more inclusive understanding of Islam that supports women’s empowerment. Overall, the study asserts that Surah An-Nahl verse 97 can be a strong foundation for supporting women's equal participation in politics and public life, encouraging a more just and equitable society